2020
DOI: 10.24867/ijiem-2020-1-248
|View full text |Cite
|
Sign up to set email alerts
|

Criticality evaluation to support maintenance management of manufacturing systems

Abstract: This paper focuses on criticality evaluation for supporting daily equipment maintenance management and the definition of medium and long-term maintenance actions to improve equipment and, therefore, productivity. These two different purposes led to the development of two different methods for criticality evaluation, using criteria adjusted for each case. The first method is based on rules for defining priorities for corrective and preventive maintenance tasks. Since a failure mode of critical equipment is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…6 show that digital services based on big-data analysis make the biggest progress in the use by manufacturing firms. These results confirm the previous findings, which show that digital technologies are the triggers for the digital transformation of manufacturing firms [26][27][28]. Furthermore, the results show that webbased offers for product utilization, web-based services for customized product configuration or product design, and digital monitoring of operating status have the highest effect on the manufacturing firms from transition economies.…”
Section: Theoretical Implicationssupporting
confidence: 90%
“…6 show that digital services based on big-data analysis make the biggest progress in the use by manufacturing firms. These results confirm the previous findings, which show that digital technologies are the triggers for the digital transformation of manufacturing firms [26][27][28]. Furthermore, the results show that webbased offers for product utilization, web-based services for customized product configuration or product design, and digital monitoring of operating status have the highest effect on the manufacturing firms from transition economies.…”
Section: Theoretical Implicationssupporting
confidence: 90%
“…Consequently, there is a demand for performance improvements, focusing on cutting costs and increasing productivity and quality levels to satisfy customers. All of this has given impetus to leading organizations around the world to adopt effective and efficient maintenance strategies, such as the TPM, over the traditional approaches of "firefighting" reactive maintenance [15]. The TPM can be defined as an improvement program that establishes a comprehensive productive maintenance system, throughout the life of the equipment, covering all fields related to the equipment.…”
Section: Background and Methodologymentioning
confidence: 99%
“…From the various literature [32,33], it has been shown that six performance parameters need to be considered that influence the above-mentioned four configuration performances. These parameters influence a flexible machine system performance, as machine availability can be an important determinant of the delivery speed and delivery dependability, because unexpected machine downtime will not only increase lead time but also disrupt the production plan [33].…”
Section: Literature Reviewmentioning
confidence: 99%